Long prodromal symptoms of neuroleptic malignant syndrome in patient with intellectual developmental disorder-A case report - Seyedehnasibeh Sadati; Forouzan Elyasi; Zahra Shyasi; Behzad Rouhanizadeh (Wiley, 2024)
Abstract Background Neuroleptic malignant syndrome (NMS) is a rare and potentially life‐threatening condition that may arise at any point during treatment and is often associated with adverse reactions to dopamine‐blocking agents. This syndrome is normally characterized by features such as muscle rigidity, alteration in consciousness, autonomic instability, and leukocytosis. Aim The aim of this study is to investigate a borderline intellectual functioning (BIF) case in which NMS with insidious disease progression and long prodromal symptoms was developed. Case Presentation The investigated patient was a 38‐year‐old female diagnosed with bipolar disorder and a variety of corresponding disorders. The patient exhibited gastrointestinal symptoms and restlessness in the weeks leading up to the study, subsequent to the administration of elevated doses of haloperidol, risperidone, and lithium. In addition, she was hospitalized for restlessness and aggressiveness in the summer of 2023. Furthermore, due to her chief complaint, she received parenteral haloperidol twice in the emergency room, subsequently experiencing fever, altered consciousness, generalized rigidity, and dysphagia. Moreover, the patient's initial creatine phosphokinase (CPK) level was 2550 IU/L, and she was hospitalized in an intensive care unit with the diagnosis of NMS for 8 days. Conclusions This case study highlights the necessity of being attentive about prodromal symptoms of NMS and emergent interventions.